BARRIERS AND DESIRE OF WESTERN BALKAN COUNTRIES TO BE INTEGRATED TO THE EUROPEAN UNION - Pipa, Donila (European Scientific Journal, ESJ, 2014)
This article aims to analyse the integration process of Western Balkan countries to be integrated to the European Union. This paper is divided into two parts. Through the comparison, the first part analyses the process of integration of the Western Balkan countries. The second part consists on a questionnaire which is conducted by the author regarding to the faith and adherence conditions that the Albanians have to the European Union. Even though the European Union is in crisis, it still remains attractive for Western Balkan countries, which will have to overcome many obstacles to become as a part of the European family. Croatia accession on July 1, 2013 is the concrete example to realize the dream of other Balkan countries that want to join the EU. EU enlargement is a completely open process, which aims to create a stronger and sustainable Europe, with an important role on the world stage and also a single, broaden and more integrated market, which intended to stimulate the economic growth, to the countries that are already members of EU, and also the other countries which are in the process of this integration. As a conclusion the accession process is necessary, because countries can’t create the future alone. This thing would be achieved only through the cooperation between each-other. The European Union is the only opportunity for the advancement of Western Balkan countries, after the fall of the Berlin Wall, and the artificial division between East and West. Only through the EU assistance, the region may have economic development, unemployment decrease, crime reduction and peace etc... Let us hope that the Western Balkans will be regenerated as part of the European family.